Therapeutics for enhanced chronic wound healing - Tan, Mandy Li Ling (Nanyang Technological University, 2023)
Chronic wounds are a major drain on healthcare resources and can lead to substantial reductions in quality of life for those affected. Moreover, they often precede serious events such as limb amputations and premature death. In the long run, this burden is likely to escalate with an ageing population and lifestyle diseases such as obesity. At present, current chronic wound management approaches can only manage wounds and are limited in their ability to actively promote the repair of chronic wounds. Although significant progress has been made in the development of different therapeutic agents, the lack of an optimal preclinical animal model is a major impediment in the translation of drugs and/or biological products to the clinic. Thus, this highlights an urgent need for the development of more relevant, robust, and reproducible animal models of delayed healing. Chronic wounds are uncommon in animals and challenging to simulate. Thus far, only the thoroughbred horses are known to suffer from chronic wounds with similar features to the human condition. However, the high economic costs of utilizing horses as an alternative model of study alongside ethical concerns, limit its feasibility. Hence, other studies have focused on identifying and isolating the main causative factors of chronic wounds, such as diabetes, ischemia-reperfusion (IR) injury and biofilm colonization. Consequently, delayed models of healing, including the streptozotocin diabetic model, skin flap model and magnet-induced IR models have emerged. However, chronic wounds are multifactorial in nature and arise through a combination of factors, which collectively overwhelm the normal healing response. While these models have been widely adopted for preclinical therapeutic testing, their relevance towards human chronic wounds remains debatable. In particular, current delayed healing models often fail to fully incorporate the key characteristics of chronic ulcers. These include features such as delayed re-epithelialization, hyper thickened non-migratory wound edges with overexpression of the gap junction protein connexin 43 (Cx43), persistent inflammation, elevated reactive oxygen species (ROS) levels, alkaline wound environment, excessive extracellular matrix (ECM) degradation at wound edges, disrupted/impaired vasculature, and sustained presence of senescent cells. Concurrently, without the protection of delivery systems, bioactive molecules are highly susceptible to degradation. Accordingly, the aim of this thesis was to explore how the effective delivery of therapeutics on a more clinically relevant animal model, can benefit chronic wound healing. Here, the methodology of exploiting the host’s response towards an oversized three-dimensional (3D) polycaprolactone (PCL)/collagen (Coll) scaffold for the development of a novel rat perturbed wound model was explored. Notably, more pronounced perturbed wound features such as a hyper-thickened non-migratory wound edge epidermis, persistent inflammation, presence of wound edge senescent cells and excessive ECM degradation in the wound edges were induced with longer scaffold contact duration, of 10 days. Upon removal of the scaffold at Day 10, the induced features remained intact, and a clean wound bed was left behind. As an extension of this work, the perturbed wound model was transferred into pigs, to enhance its clinical relevance and contribute to the establishment of a two-species preclinical testing platform. Here, the perturbed model was successfully established in pigs. Notably, many aspects of human chronic wound were recapitulated in pig perturbed wounds, such as delayed wound closure, chronic inflammation, overexpressed Cx43, high senescence levels and excessive wound edge ECM degradation and hindered ECM deposition in wound beds. Leveraging on the pig perturbed wound model, different Cx43-based therapeutics, were then explored. In this thesis, the efficacy of Cx43 antisense oligodeoxynucleotide (asODN), delivered in pluronic gel, was tested in the pig perturbed wound model. Here, transient downregulation of Cx43 expression in the leading-edge keratinocytes as well as in perturbed wound edges, resulted in accelerated re-epithelialization and a significant decrease in inflammatory cell infiltration, especially at early timepoints. The current results support the therapeutic potential of Cx43asODN in promoting chronic wound healing. However, both pluronic gel and Cx43asODN were speculated to undergo rapid degradation in the harsh perturbed wound environment, accounting for the transient downregulation seen in this study. Therefore, an alternative delivery system, capable of facilitating sustained delivery of Cx43asODN might be necessary to achieve improved wound healing outcomes. Other than Cx43asODN, the effect of Tonabersat which is a connexin hemichannel blocker was also evaluated in the pig perturbed wound model. In this study, localized delivery of Tonabersat, in pluronic gel, resulted in significantly improved functional outcomes. In particular, Tonabersat treatment led to significantly faster wound closure rates as well as reduction in both inflammatory cell infiltration and senescent cell levels in pig perturbed wounds. As mentioned above, an alternative delivery strategy to improve the bioavailability of Cx43asODN in perturbed wounds was necessary. Here, the use of chitosan as a coating material was explored as a strategy to increase the adsorption of asODN onto electrospun PCL scaffolds and thereby achieve sustained release of Cx43 asODN. Here, the surface modification of PCL scaffolds with chitosan significantly enhanced the adsorption of Cx43asODN and resulted in a sustained and significant release of asODNs over a 5-day period. In the rat perturbed wound model, this corresponded with a sustained downregulation of Cx43 protein levels at the epidermal tongue, wound edge, and perturbed wound beds. Consequently, the rate of re-epithelialization was significantly improved, and inflammation is reduced. With respect to Molecule T, delivering higher concentrations of this drug could further promote perturbed wound healing. However, a corresponding increase in organic solvents could be toxic to cells. This highlights the need for an alternative delivery system, capable of delivering high concentrations of Molecule T while allowing the removal of potentially toxic organic solvents. In this work, a particle-based delivery system was employed using an emulsion-based method to encapsulate Molecule T within PLGA particles. Here, the organic solvent used to dissolve both PLGA and Molecule T was removed, as a part of the process involved in the formation of the PLGA particles. Consequently, delivery of the PLGA-Molecule T particles in the rat perturbed wound model promoted wound healing, without any adverse effects. In particular, Molecule T-treated wounds were observed to have faster re-epithelialization rates. Concurrently, Molecule T application also led to reductions in NLRP3 and caspase-1 levels. Taken together, this thesis demonstrated the potential of the newly developed perturbed wound model in both rats and pigs, as a clinically relevant therapeutic testing platform. Importantly, this model was successful in recapitulating many features of human chronic wounds. Accordingly, different therapeutics, and their respective delivery systems, targeted at different aspects of the pathophysiology of chronic wounds can be tested in this model. This would allow the evaluation of how each therapeutic could potentially promote perturbed wound healing and thus provide critical information on its performance upon translation to human chronic wounds.